Kernel principal component analysis and differential non-linear feature extraction of pesticide residues on fruit surface based on surface-enhanced Raman spectroscopy - Shi, Guolong; Shen, Xinyi; Ren, Huan; Rao, Yuan; Weng, Shizhuang; Tang, Xianghu (Frontiers in Plant Science, 2022)
Surface-enhanced Raman spectroscopy (SERS) has attracted much attention because of its high sensitivity, high speed and simple sample processing, and has great potential for application in the field of pesticide residue detection. However, surface-enhanced Raman spectroscopy is susceptible to the influence of complex detection environment in the detection of pesticide residues on the surface of fruits, facing problems such as interference from the spectral peaks of detected impurities, unclear dimension of effective correlation data, and poor linearity of sensing signals. In this paper, the enhanced raw data of the pesticide thiram residues on the fruit surface using gold nanoparticle solution are formed into the raw data set of Raman signal in the IoT environment of Raman spectroscopy principal component detection. Considering the nonlinear characteristics of sensing data, this paper adopts kernel principal component analysis (KPCA) including radial basis function (RBF) to extract the main features for the spectra in the ranges of 653~683 cm−1,705~728 cm−1 and 847~872 cm−1, and discusses the effects of different kernel function widths (σ) to construct a qualitative analysis of pesticide residues based on SERS spectral data model, so that the SERS spectral data produce more useful dimensionality reduction with minimal loss, higher mean squared error for cross-validation in nonlinear scenarios, and effectively weaken the interference features of detecting impurity spectral peaks, unclear dimensionality of effective correlation data, and poor linearity of sensing signals, reflecting better extraction effects than conventional PCA models.